Aspectos morfológicos, agronômicos, e nutricionais de acessos de mangarito - Thamara Figueiredo Menezes Cavalcanti (2011)
This study aimed to characterize morphology, agronomic and nutritionally five accessions of tannia. The experiment was conducted in the research garden of the Institute of Agricultural Sciences, UFMG, in Montes Claros, Minas Gerais, in the period of June 2010 to June 2011. It was used the experimental design of randomized blocks with five treatments and four replications, a total of 20 plots. The treatments consisted of five accessions of tannia obtained at the Universidade Federal of Viçosa-MG (Viçosa 1, Viçosa 2 and Viçosa 3), in the Universidade Federal da Grande Dourados-MS (Dourados), besides of local access (Montes Claros). The spacing used was 0,5 m between rows and 0,5 m between plants. The main morphological characteristics evaluated were the plant height (cm); link petiole; leaf blade shape; angle of the basal rib in relation to midrib; petiole length (cm), petiole coloration; petiole sheath length (cm); shape and flesh color of the pulp of the corms and cormels. The main agronomical characteristic evaluated were total and commercial yield; average fresh mass of commercial cormelos; commercial cormels number per plant; productivity of cormels in the classes large ( 30 mm), medium (20-29 mm), small (10-19 mm) and reject (<10 mm). In the nutritional characterization there were analyzed the levels of N converted into protein, of Ca, Mg, Mn, P, Fe, Na, K, Cu, Zn, S and B in corms and cormels separately. There was no variation among acesses concerning the morphological characterization, with the exception of access Dourados which presented red streaks in the upper portion of the petiole to the midrib. The study revealed leaf blade of the hastada type in all the materials and underground stem and its lateral shoots were classified as corms and cormels for presenting visible internodes. The five evaluated accesses in this study were identified as X. riedelianum due to the agronomic characteristics, highlighting the shape and length of the leaf blade. As for agronomic evaluations, the access Viçosa 1, Montes Claros, Viçosa 3 and Viçosa 2 showed the best responses as overall productivity and the productivity of cormels. The highest commercial yields were obtained by hits Viçosa 1, Montes Claros and Viçosa 3, in relation to access Dourados. There was no statistical difference for the productivity of corms and fresh and dry weight of commercial cormels. Viçosa 1 had the highest number of commercial cormelos per plant, it did not differ of the accesses Viçosa 2 and Viçosa 3 and overcoming access to Montes Claros and Dourados. The five accesses studied showed variability for nutritional composition. The levels found in Ca, P, Fe and Zn have shown promise regarding the main starchy vegetable crops. The corms showed levels of phosphorus, potassium and sulfur in cormelos higher than in all accesses. The calcium, magnesium, sodium, zinc, and manganese excelled in the cormels in all the accesses.